Examining the Academic Outcomes of 2SLGBTQ+ University Students in Ontario: Microaggressions and the Meditating Role of Psychological Well-Being - Woodford, Michael R.; Vo, Tin D.; Oakes, Harrison; Smith, Brandon R. G. (Canadian Journal of Higher Education / Revue canadienne d'enseignement supérieur)

(untitled) (Canadian Society for the Study of Higher Education, 2025)
Research on trans and LGBQ microaggressions on campuses and their consequences has grown, yet this literature is primarily from the United States and the effects of microaggressions on academic outcomes remain generally under-investigated. Trans/LGBQ microaggressions can negatively affect students’ psychological well-being, which matters for their academic outcomes, suggesting well-being might mediate the impact of microaggressions on academic outcomes. Using a convenience sample of 2SLGBTQ+ university students from Ontario (N = 3,344), we examine the association between trans/LGBQ microaggressions and academic satisfaction and school avoidance, testing if they are mediated by psychological well-being, controlling for demographics. We report findings for trans/LGBQ microaggressions separately to centre trans and gender-diverse (TGD) students’ experiences. For both groups, we found that microaggressions were associated with poorer academic outcomes. Except for one pathway among TGD students, we found that psychological well-being mediated the microaggressions–academic outcome relationships. We offer implications to support student services that are responsive to 2SLGBTQ+ students.